Understanding industrialised house building as a company's dynamic capabilities. Issue 1 (4th August 2020) - Stehn, Lars; Engström, Susanne; Uusitalo, Petri; Lavikka, Rita
Abstract : Purpose: To further the understanding of industrialised house building (IHB) from a temporal, emergent corporate-ability perspective, this study aims to trace the build-up of corporate assets in an IHB company over time. The research draws on dynamic capabilities, acknowledging not only what assets the company have developed and currently are exploiting, but also how these assets were develop and managed (i.e. enhanced, combined, protected and potentially reconfigured) to sustain long-term competitiveness. Design/methodology/approach: A case study design was used to form a narrative that covers the evolution of an IHB company over a 25-year period. Corporate archival material, analysis of original data from a large number of research studies during 1993-2013 and retrospective reflections of owners and managers, including crosschecking interpretations of archival material, developed and triangulated the narrative. Findings: The study presents rich empirical findings on the build-up of corporate assets. Starting from a successive process of exploration and exploitation formation of dynamic capabilities eventually played out into an exponential dynamic capability build-up. The IHB case company displays the ability to not only continuously exploit and renew resources and competences, but also to sense, seize and reconfigure cumulative assets over time. The exponential development of dynamic capabilities resonates to literature on higher-order dynamic capabilities implying that: the accumulated and higher-order dynamic capabilities are difficult to imitate and a (any) company must possess higher-order dynamic capabilities to be able to exploit and/or take up IHB. Originality/value: The study is complementing and potentially challenging frequent framings of the IHB concept. Previous research has addressed and characterised IHB mainly by encapsulating a moment in time and, thus, characteristics are momentary and represent static views on IHB. However, IHB has seen a strong development over the past 25 years, and the study reflects on this development from the perspective of one of the IHB-forerunner companies in Sweden. By exploring from a company perspective the developments, reconfiguration and capacity to develop/reconfigure over time in a changing environment, the study introduces an alternative understanding of IHB as dynamic capabilities.